Laju Pertumbuhan Ikan Kerapu Bebek Cromileptes altivelis yang Dipelihara dalam Keramba Jaring Apung - Safar Dody; Dinawanti La Rae (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Growth Rate of Humpback Grouper Cromileptes altivelis Cultured in Floating Net Cages. Humpback Grouper Cromileptes altivelis fish farming has good opportunities in the future, although still experiencing problems in its cultivation. One of the parameters that needs to be considered is the stocking density associated with the cage area. The purpose of this study was to determine the appropriate stocking density to generate optimum growth of Humpback Grouper cultivated in floating net cages. The study was conducted using the experimental method with 3 treatments and 3 replications. There were 9 cages used with the size of 1 x 1 x 1.5 m3 and a mesh size of 0.5 inches. The study was conducted in the waters of Banda Neira, Maluku, with the condition of the waters during the experiment, such as salinity which ranged from 33.2 to 34.6‰, water temperature ranged from 25 to 31°C, pH ranged from 7 to7.5, current speed 0.32–3.97cm/s, and water clarity was 14.29 to 20 m. The feed was trash fish given twice a day, in the morning and afternoon as much as 10% of total body weight of fish. After 4 months of cultivation, the absolute growth was best demonstrated by the treatment with stocking density of 25 fish/cage, which was 18.22 g, while the lowest (13.25 g) was shown by the treatment with stocking density of 75 fish/cage. The specific growth rate in the treatment of 25 fish/cage reached 1.34%/day, while the treatment of 50 fish/cage and 75 fish/cage reached 1.18%/day and 0.97%/day respectively.